Invasive papillary thyroid carcinoma appearing in a thyroglossal duct cyst: A rare case report - Nguyen, Van Mao; Ngo, Quy Tran; Tran, Thi Nam Phuong; Tran, Nam Dong; Le, Thi Thu Thao; Tran, Van Bao; Vo, Thi Hanh Thao; Nguyen, Phuong Thao Tien; Tran, Anh Hung (Tạp chí Y Dược Huế, 2024)
Thyroglossal duct cyst (TGDC) is the most frequent congenital anomaly of the thyroid gland. The existence of primary malignancy originating from this cyst is uncommon, accounting for less than 1% of all cases. Because of its rarity, there is no universal consensus regarding optimal treatment option. We present a case of a 59-year-old woman with a 25x20 mm mass in the anterior area of the neck that gradually increased in size over six months. A total thyroidectomy and Sistrunk procedure (SP) were performed. Postsurgery histologic evaluation confirmed papillary carcinoma of the TGDC invading adjacent muscle tissue